2017
DOI: 10.1590/0100-29452017635
|View full text |Cite
|
Sign up to set email alerts
|

Production of Guava Mini-Grafted on Intra or Interspecific Rootstock

Abstract: -Mini-grafting is a type of grafting that has been indicated to increase efficiency of forest and fruit species propagation. the aim of this study was to evaluate the mini-grafting technique as a method for propagation of guava grafted on intra or interspecific rootstock. The experimental design was randomized blocks, with four treatments, five replications and plots consisting of ten plants, in a 2 2 factorial arrangement, and factors consisted of rootstocks and canopy cultivars. Rootstocks used were Psidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…Variety 'Pera' sweet orange stood out in rootstock diameter, because it presented higher means in this variable (Table 6), different from what Campos et al (2017) have observed 120 days after minigrafting applied to guava, when rootstock diameter was similar in all combinations involving crown cultivar and rootstock.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Variety 'Pera' sweet orange stood out in rootstock diameter, because it presented higher means in this variable (Table 6), different from what Campos et al (2017) have observed 120 days after minigrafting applied to guava, when rootstock diameter was similar in all combinations involving crown cultivar and rootstock.…”
Section: Discussioncontrasting
confidence: 67%
“…Another factor to be considerate into account is the compatibility between involved tissues given their great influence on the success of overall grafting techniques. This factor also has to be considerate into account, since it relates the affinity between crown and rootstock (Campos et al, 2017). Overall, this is an important factor to achieve a successful grafting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there was reported the intraspecific mini-grafting of P. guajava and ''Psidium''/ p. guineense, with efficiency of 52% and 82%, using guava "Cortibel 1"/Psidium guineense and guava "Paluma"/P. guineense, respectively, showing the capacity of guava to graft with another species of Psidium (Campos et al, 2017). In our study, after 1-year of in vitro-grafting of P. guajava/P.…”
Section: Resultssupporting
confidence: 52%
“…Another important result is that shoot diameter responded linearly to the GA concentration applied in both evaluated seasons (Figure 4C). Shoot diameter is important for making herbaceous mini-cuttings, since, after rooting, if these seedlings are used as rootstocks, this step can occur more quickly according to stem thickness (Gomes et al, 2010;Campos, Marinho, Portella, Amaral, & Carvalho, 2017), as it allows for faster grafting. Matos et al (2015) evaluated different concentrations of GA in eucalyptus clones and demonstrated that the treatment with 150 mg L -1 provided a 29% increase in stem diameter in comparison to control.…”
Section: Plantsmentioning
confidence: 99%